2005
DOI: 10.1111/j.1439-0426.2005.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasites as biological indicators of population structure of Halobatrachus didactylus on the Portuguese coast

Abstract: Summary A total of 366 Halobatrachus didactylus (Bloch & Schneider 1801) individuals were obtained between September and November 2000 from commercial fishing vessels at eight localities along the Portuguese coast and analysed for metazoan parasite infections. Three species of parasites were found: Hysterothylacium aduncum Rudolphi 1802; Progrillotia dasyatidis Beveridge et al. 2004, which constitutes a new host record for the Lusitanian toadfish; and Nerocila orbignyi Guérin‐Méneville 1829. Prevalence and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Murta, 2000;Saborido-Rey and Nedreaas, 2000;Oliva and Ballón, 2002;Oliva and Gonzalez, 2004;O'Reilly and Horn, 2004;Marques et al, 2005), simultaneously (e.g. George-Nascimento and Arancibia, 1994) and in conjunction with genetic markers (Cabral et al, 2003a;McClelland et al, 2005;Pinheiro et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Murta, 2000;Saborido-Rey and Nedreaas, 2000;Oliva and Ballón, 2002;Oliva and Gonzalez, 2004;O'Reilly and Horn, 2004;Marques et al, 2005), simultaneously (e.g. George-Nascimento and Arancibia, 1994) and in conjunction with genetic markers (Cabral et al, 2003a;McClelland et al, 2005;Pinheiro et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches pointed out Hysterothylacium infection all around the world including the Mediterranean Sea (Petter and Cabaret 1995;Petter and Maillard 1988;Costa et al 2004;Anderson 2000;Henderson et al 2002;Marques et al 2005;Valero et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…However, in spite of these studies, the existence of a possible relationship between the fish populations from the three areas (Sesimbra, Madeira and azores) is not fully known. a number of studies has shown that parasites may be used as biological tags in the discrimination of fish stocks from different geographical localities (Marcogliese et al, 2003;oliva et al, 2004;Marques et al, 2005;Melendy et al, 2005;McClelland and Melendy, 2007;Mackenzie et al, 2008;Ferreira Marques et al, 2009). review articles on this subject, including the procedures and methods employed in the use of parasites as biological tags, may be found in Mackenzie and abaunza (1998;, Mosquera et al (2000), Mackenzie (2002, 2004), timi (2007), abaunza et al (2008) and lester and Mackenzie (2009.…”
mentioning
confidence: 99%